Plasma amisulpride levels in schizophrenia or schizoaffective disorder - Bergemann, Niels; Kopitz, Jürgen; Kress, K. R.; Frick, Alex (European neuropsychopharmacology, 2004)
The atypical antipsychotic drug amisulpride is a benzamide with specific antagonistic properties, which target dopamine D2 and D3 receptors, preferentially in the limbic system. Amisulpride is readily absorbed from the gastrointestinal tract, distributed to all body systems with little binding to plasma proteins. Elimination occurs mainly through the kidneys as unchanged drug. In contrast, hepatic metabolism is of minor significance and primarily yields two inactive metabolites. Very little is known about the plasma concentrations of amisulpride in patients at varying oral doses or about clinically relevant interactions with co-medication. The aim of the present investigation was to elucidate the factors, which affect amisulpride levels in schizophrenic patients. The plasma amisulpride levels of 85 patients with schizophrenia or schizoaffective disorder (mean age: 34.0±11.4 years; 40 women, 45 men) were assessed by high-performance liquid chromatography (HPLC) with fluorometric detection. The average daily dose of amisulpride was 772.3 mg (S.D. 346.7 mg) and the mean amisulpride plasma concentration was 424.4 ng/ml (S.D. 292.8 ng/ml). The interindividual variance of the amisulpride plasma concentration was high; furthermore, the plasma concentration increased linearly with the daily oral dose (r=0.50, p<0.001). Age and gender showed a significant effect on the dose-corrected amisulpride plasma concentrations-older patients and women had higher dose-corrected amisulpride plasma concentrations than younger patients and men. However, cigarette consumption had no effect on the amisulpride plasma concentrations. Regarding co-medication with lithium and/or clozapine, significantly higher amisulpride plasma concentrations were found as compared to monotherapy, whereas other co-medications such as benzodiazepines and various conventional antipsychotics had no effect on the amisulpride plasma concentrations. The results, the possible pathomechanisms and the clinical relevance are discussed. The findings need to be confirmed in larger patient samples and with a wider range of co-medications.
Online 14 November 2003
Gesehen am 15.12.2020